Dynamic duets : the best pop collaborations from 1955 to 1999 - Leszczak, Bob, 1959- (Rowman & Littlefield, 2016)
The second half of the twentieth century saw a great number of powerful vocal pairings as short-lived, but undeniably magical collaborations. With firsthand interviews from many of the artists, readers will enjoy the back story about which duos got along well and which did not, which stayed together or kept in touch, and vice versa. Arranged alphabetically from Bryan Adams to Dottie West, Dynamic Duets gives the back stories on all of the pairings that cracked Billboard's Top 40 between 1955 and the end of the century. The book includes photographs of many of the records and/or the performers,